Customer relationship management of web-based education: A case study for metu-online - (:unkn) unknown (Middle East Technical University, Faculty of Engineering, 2005)
Web-based education is a preference of many instructors and students of today's education systems. There exist a few attempts to design Customer Relationship Management (CRM) systems for such education organizations. "Customers" of such organizations, namely students, instructors, visitors, managerial and technical teams, have different needs and requirements. METU-Online is a distance education platform developed and maintained by the Informatics Institute of Middle East Technical University (METU). In this study, we analyse distance education and CRM, present the METU-Online system and the CRM conceptual model developed for it.
Keywords: CRM; Distance Education; Web-Based Education